TYPES AND IMPORTANCE OF SECONDARY RAW MATERIALS FROM POLYMER WASTE (Archive of Conferences, 2020)
This article discusses the polymer product, its types, types of waste and their processing.Among the wastes, the most common waste in recent times is polymer products. It is possible to obtain secondary raw materials as a result of processing of polymer products. The use of secondary raw materials in various industries is much cheaper than primary raw materials.More than 50% of polymer products have recently been recycled.